Explicit fluid–flow–solid interaction. (4th August 2014) - Muller, A.; Jacob, N.
The solution of the Navier–Stokes equations is a boundary value problem. That means, from the engineering point of view, that the geometric boundaries and Diriclet and/or Neumann conditions have to be specified. In real fluid flow problems there is in general at least the geometry of the problem well defined. But in general, strictly speaking, there is principally always an interaction between the fluid motion (i.e. the resultant pressure) and the surrounding body. This interaction is of course often very small and can mostly be neglected. But there are also relevant cases where the interaction between fluid and surrounding media is essential, for example in the mechanism of blood flow through a human body. Up to now there are only special purpose codes commercially available which have the capability to cover the possibility of fluid–flow–solid interaction. The remaining possibility is, at least so far, to couple externally in an iterative way fluid and solid computational analysis. This seems to be a costly procedure, but it has one advantage: the most efficient codes for CFD as well as for structural mechanics can be used to ensure most reliable results if there is a way that they can be coupled. This paper shows an example of this procedure coupling a CFD–code with both a finite element and a boundary element code. We discuss the costs and computational strategies of this procedure and show examples of a steady state as well as a transient calculation.